BISPHENOL S INDUCED CYTO-GENOTOXIC EVALUATION IN Eisenia fetida THROUGH MICRONUCLEUS AND COMET ASSAYS - Umar Nazir; Asia Iqbal; Muhammad Muddassir Ali; Kashif Ali; Aftab Hussain; Sumaira Abbas; Sidra Ashraf; Beenish Aftab; Hafiza Ghulam Fatima (Journal of Animal and Plant Sciences, 2026)
Bisphenol S (BPS), the most commonly used alternative to bisphenol A (BPA), is widely present in various consumer products. This study was designed to investigate the BPS-induced cyto-genotoxicity in E. fetida, an important soil indicator. Earthworms were categorized into four experimental groups and one control group (n=10/group), and exposed to different concentrations of BPS (50, 100, 150 and 200 mg/mL). The median lethal concentration (LC50) of BPS was calculated as 50 mg/mL using Probit analysis estimating the concentration corresponding to the 50% mortality. Both cytotoxic and genotoxic assays (micronucleus and comet) showed a concentration-dependent increase in micronuclei frequency and DNA damage in earthworms with significant differences (p < 0.05) between the control and BPS-treated groups. At 200 mg/mL, the greatest level of DNA damage (92.0 ± 1.41) and micronuclei frequency (113.5 ± 4.24) were observed. The findings of this study showcase the potential cyto-genotoxicity and hazardous risks due to BPS exposure and emphasize the need for its cautious use and stringent regulation regarding BPS in consumer products.
Keywords: Biomarkers; DNA Damage; Endocrine disrupter; Oxidative stress; Soil ecotoxicology